Learning Style among Multi-Ethnic Students in Four Selected Tertiary Institutions in the Klang Valley - Syed Mohamad, Syed Jamal Abdul Nasir (2006)
Learning style is affected by individual differences such as gender, academic and cultural background (Hyland, 1993). However ethnicity is indicated to be the main factor in influencing learning styles (Park, 2000 and Ewing, 1993). In relation to the above statements, Malaysia, a multiracial country provides a rich source of information in finding the relationship between ethnicity and learning styles. Although the three major races, the Malays, Chinese and Indians, are given equal opportunities to further their studies in the institutions of higher learning in the country they were brought up in different cultural backgrounds that influenced the development of their own style of learning. This study examined the learning styles of multi-ethnic students’ in four selected universities in Klang Valley in terms of gender, program of studies and academic achievement levels. Using a modified Honey and Mumford learning Style Questionnaire, 291 valid responses from two public and private universities were subjected to further quantitative analyses of the study. The result of the descriptive analyses revealed that the multi-ethnic students exhibited all the four learning styles that were Activist, Reflector, Theorist and Pragmatist style. Reflector style was found to be the most preferred learning style by the multi-ethnic students while the Activist style was the least preferred. The male and female students demonstrated different patterns of learning styles even though the Reflector style was the most preferred style of both genders. The arts and science students seemed to exhibit similar patterns of learning styles except for the Malay students. The students from IPTA and IPTS too demonstrated similar pattern of learning styles. However the result of Chi-Square Test showed that there was no significant difference in the learning styles among ethnicity, between genders and program of studies. Similarly, the ANOVA did not show any significant difference in the academic achievement among students with different learning styles. Based on the results, five conclusions are made. First, the result of the study is congruent with the learning style theories by Kirton (De Ciantis and Kirton, 1999), Kolb (1984), and Honey and Mumford (1986). Second, The Malay,Chinese and Indian are considered as all-rounder learners. Third, the learning styles have no relationship with academic achievement. Fourth, ethnicity has no bearing on learning styles among multi ethnic tertiary students. Finally, the learning styles are not significantly different between male and female students, and between science and arts students. The study has contributed new knowledge in the literature of learning styles especially the one based on Malaysian context. Besides providing more insight in understanding multi-ethnic students’ learning styles, the study also provides recommendations for higher institutions in Malaysia, providers of extension education and also creates the need for further research in this area.